Computer Crime in the Digital Age literature review of scientific articles from 2019 to 2024 - Gavilanes, Mgs. Luis Antonio Villalta; Villalta, Mgs. Leonardo Orleans Labre; Gavilanes, Mgs. Adriana Mercedes Villalta; Llauce, Dra. Cecilia Teresita de Jesús Carbajal (Journal of Ecohumanism, 2024)
This systematic review study was conducted from 2019 to 2024 following the guidelines of the PRISMA protocol through an exhaustive search in Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex, the University César Vallejo library, and other databases, and aims to identify current trends and challenges in the prevention of cybercrime in Ecuador. The results show that, despite legislative efforts, cybercrime remains a growing problem in the country. The findings of this research have important implications for public policy formulation, investment in technology, and cybersecurity education in Ecuador. Lack of user awareness, insufficient resources for law enforcement, and the rapid evolution of technologies were identified as key factors. Public policies that promote cybersecurity education, investment in protection technologies, and collaboration between public and private institutions are recommended. In conclusion, this systematic review underscores the need to adopt a multidisciplinary and proactive approach to combat cybercrime in Ecuador.